YURISDIKSI INDONESIA DALAM MASALAH PENCEMARAN LAUT OLEH MINYAK BUMI DARI KAPAL ASING DI LAUT TERITORIALNYA BERDASARKAN KONVENSI PBB TENTANG HUKUM LAUT 1982 - Imam Subekti (Qistie Jurnal Ilmu Hukum, 2011)
1982 UN Convention about the marine law, Indonesia's nasional jurisdiction as acoastal state is based on provisions of domestic law which is guareenteed by theconvention that is hitting countries may implement establish its sovereignty in itsterritorial sea legislation to prevent, reduce and control marine pollution for theisland nation can be said contain a system that provides an opportunity that ismore easier for the protection of marine areas of Indonesia, the possibility of seapollution by oil spills. In the case the Indonesia's national legal provisionscontained in the Decree of the Minister of Transportation No. KM 86 of 1990 onthe Prevention of Marine Pollution by oil from ship and No. 4/Prp Act of 1960 onIndonesia Waters, generally gives a lot of benefit to countries that have a duty toprotect and preserve the marine environment.Keywords: Marine Oil Pollution from Foreign Ship